COMORBIDITY IN CORONARY HEART DISEASE PATIENTS UNDERGOING BYPASS GRAFTING: AN EXPERIENCE OF TWO SURGERY CENTERS - N. L. Barbarash; V. Yu. Semjonov; I. V. Samorodskaya; М. V. Evseeva; N. A. Rozhkov; A. N. Sumin; L. S. Barbarash (Российский кардиологический журнал)
Aim. To evaluate the prevalence  of comorbidities in patients  undergoing  coronary bypass grafting (CBG) in two surgery clinics of Russia.Material and methods. Into retrospective study, done based  upon the charts data of A. N. Bakulev Scientific Center for Cardiovascular Surgery (A. N. Bakulev SCCVS) and  Research  Institute  for  Complex  Issues   of  Cardiovascular  Diseases,  1702 patients  included (1358 males, 344 females) from Bakulev SCCVS and 1159 (895 males,  264  females)  patients  from RICICD, who had  underwent  CBG, including multiple surgeries, during 2014-2015. Comparative analysis was performed  of the prevalence of comorbidity and combination pathology.Results. The main background pathology in general group of patients was arterial hypertension   (AH) — 2322  (81,2%)  cases. In more  than  a  half  of  cases, in anamnesis there  was myocardial infarction (MI) — 1719 (60,1%), of those  in 250 (8,7%) patients  — with left ventricle aneurysm.  Lower extremities atherosclerosis was found  in 13,8%  cases. Stroke  anamnesis had  5,6%  patients.  Prior carotid endarterectomy (CEE) was found in 30 (1,0%) cases, percutaneous intervention — 190 (6,6%) patients.  The most common comorbidity in general  group was type 2 diabetes — 505 (17,6%) cases. Chronic obstructive pulmonary disease (COPD) was found in 352 (12,3%) patients,  erosions  and  ulceration  of gastro-intestinal tract (GIT) — in 10,6% cases.Patients  of RICICD were older (62,5±7,8  vs 60,8±8,5  y.o., p=0,003),  had  AH more commonly (83,1 vs 79,8%, p=0,02), as stroke anamnesis (7,2 vs 4,5%, p=0,002), prior MI (66,8 vs 55,5%, p<0,05), prior PCI (12,9 vs 2,4%, p<0,05), COPD (13,8 vs 11,3%, p=0,044), GIT ulceration (15,2 vs 7,5%, p<0,05) in comparison to Bakulev SCCVS. Bakulev SCCVS patients had 1,5 times more prevalently the atherosclerotic lesion of lower extremities  (15,9  vs 10,6%,  p<0,05),  prior CEE was done  3,7 times  more prevalently than in RICICD (1,5 vs 0,4%, p=0,007), more commonly the combination intervention was done: CBG with valvular correction (11,3 vs 6,7%, p<0,05).Conclusion. The prevalence of comorbidity is determined by the age of patient, as regional specifics of morbidity in population hospitalizing to one or another surgical center.